(untitled) (Journal of Parents and Teachers, 2026)
Effective time and task management presents a constant challenge for school leaders, who often admit that they need to organise themselves more effectively. This report introduces the PERT (Program Evaluation and Review Technique) system, a graphical and user-friendly methodology based on lines, dots and numbers that helps to improve project design.